LoopTag FRET Probe System for Multiplex qPCR Detection of Borrelia Species - Henning Hanschmann; Stefan Rödiger; Toni Kramer; Katrin Hanschmann; Michael Steidle; Volker Fingerle; Carsten Schmidt; Werner Lehmann; Peter Schierack (Life, 2021)
Background: Laboratory diagnosis of Lyme borreliosis refers to some methods with known limitations. Molecular diagnostics using specific nucleic acid probes may overcome some of these limitations. Methods: We describe the novel reporter fluorescence real-time polymerase chain reaction (PCR) probe system LoopTag for detection of Borrelia species. Advantages of the LoopTag system include having cheap conventional fluorescence dyes, easy primer design, no restrictions for PCR product lengths, robustness, high sequence specificity, applicability for multiplex real-time PCRs, melting curve analysis (single nucleotide polymorphism analysis) over a large temperature range, high sensitivity, and easy adaptation of conventional PCRs. Results: Using the LoopTag probe system we were able to detect all nine tested European species belonging to the Borrelia burgdorferi (sensu lato) complex and differentiated them from relapsing fever Borrelia species. As few as 10 copies of Borrelia in one PCR reaction were detectable. Conclusion: We established a novel multiplex probe real-time PCR system, designated LoopTag, that is simple, robust, and incorporates melting curve analysis for the detection and in the differentiation of European species belonging to the Borrelia burgdorferi s.l. complex.